COMPARISON OF NONLINEAR MODELS TO DESCRIBE GROWTH CURVES IN THE CATALAN GOAT - Parés-Casanova, Pere M. (2014)
The aim of this study was to evaluate the growth curves for males and females in the Catalan goat population using different non lineal models (Logistic, von Bertalanffy and Gompertz). The models were applied to the study of body weight of 77 animals (21 males and 56 females of various ages). Fitness was different for each model where the logistic model was the best for males and the von Bertalanffy for females. Still, the logistic model tends to overestimate the initial weight of the animals.